(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper provides a comparative analysis of the global legal landscape of LGBTQIA+ rights in 2025, highlighting both significant progress and persistent challenges. While over 35 countries have legalized same-sex marriage and enacted anti-discrimination protections, approximately 65 nations still criminalize same-sex relations, with penalties ranging from imprisonment to death. Through case studies from India, Taiwan, South Africa, and the United States, the paper demonstrates how courts and legislatures have advanced equality by dismantling discriminatory laws and affirming constitutional rights. At the international level, frameworks such as the ICCPR, the Yogyakarta Principles, and regional human rights systems have reinforced protections, albeit with limited enforcement mechanisms. However, setbacks—including Uganda’s Anti-Homosexuality Act, Hungary’s restrictive constitutional amendments, and resurgent far-right populism in Europe—illustrate the fragility of progress. The study concludes that while international norms provide aspirational frameworks, transformative change continues to depend on domestic political will, judicial activism, and civil society resilience. Ultimately, the trajectory of LGBTQIA+ rights remains a paradox of unprecedented advancements alongside intensified backlash.